Factors influencing Nigerian men's decision to undergo prostate specific antigen testing - Enaworu, Oghenetejiri Ubrurhe (Afr Health Sci, 2016)
BACKGROUND: Prostate cancer is a major cause of cancer death in Nigerian men. Attempts to reduce mortality from prostate cancer have focused mainly on early detection of the disease by the use of PSA testing. As a result of the increased incidence of prostate cancer in Nigeria despite the widespread availability of testing facilities, it became pertinent to understand the salient factors that prompt Nigerian men to go for prostate cancer testing. OBJECTIVE: This study explores the factors that influence a group of Nigerian men's decision to go for Prostate Specific Antigen (PSA) testing. METHODS: Following ethical approval, semi structured interviews were conducted with a group of 10 men who had PSA test following consultation with their doctor with signs and symptoms at the University of Benin Teaching Hospital from July to August, 2010. Interview transcripts were analysed by employing steps proposed by Collaizi (1978). RESULTS: Five themes were identified: the symptoms experienced, the influence of friends and relatives, older age associated with increased awareness, accessibility to testing services and the knowledge of the PSA test. CONCLUSION: The study revealed that there continues to be a considerable lack of awareness and knowledge about prostate cancer and screening.